Analisis Dan Perancangan Sistem Informasi Pelayanan Pernikahan Pada Kantor Urusan Agama (KUA) Kecamatan Jambi Timur - Arafah, Tuty; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2020)
Research at the Office of Religious Affairs (KUA) of East Jambi Sub-district engaged in the field of Religion was conducted to analyze weaknesses the running system, in order to overcome the problems that existed at the Office of Religious Affairs (KUA) of East Jambi District. In the process of data collection at the Office of Religious Affairs at this time, such as marriage registration or data on marriage requests, handwriting is still carried out by officers. Errors in writing that require officers to make repeated data changes and require a long recording process. The absence of an appropriate data storage area, causing data search and report generation to be delayed. Based on the above problems, the author tries to design a prototype system that is expected to help employees to manage the data needed at the Office of Religious Affairs (KUA) of East Jambi District and can provide good service to the community. The research method used in this study is field research, They are observation, interviews, and library research. System design is also done using DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and data dictionary (Data Dictionary). The results of the study show that there are several weaknesses of the system that is running, which there is no appropriate data storage area causing data searches and report generation to be delayed due to data that cannot be found.